2006
DOI: 10.1136/bjo.2005.082768
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peripheral retinal ablation with cryotherapy versus diode laser photocoagulation on axial length in the growing rabbit eye

Abstract: Peripheral retinal cryotherapy causes a significantly greater elongation of the eye compared to diode laser photocoagulation in a rabbit model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…Whitmore et al reported that transcleral cryotherapy of the anterior retina in young rabbits slowed the growth of the anterior and posterior segments of rabbits eyes [211]. Later Axel-Siegel et al reported that cryotherapy of the peripheral retina in rabbits resulted in elongation of the eye [5]. …”
Section: Diverse Tissuementioning
confidence: 99%
“…Whitmore et al reported that transcleral cryotherapy of the anterior retina in young rabbits slowed the growth of the anterior and posterior segments of rabbits eyes [211]. Later Axel-Siegel et al reported that cryotherapy of the peripheral retina in rabbits resulted in elongation of the eye [5]. …”
Section: Diverse Tissuementioning
confidence: 99%
“…Randomized trials by Ng and Connolly showed laser photocoagulation to be as effective as cryotherapy [2][3][4][5]. Laser treatment was also found to be less destructive to the ocular coats with a significantly lower myopic refractive error and a functional visual difference that was maintained over 10 years [2,[6][7][8]. Conventional treatment strategy using laser photocoagulation is restricted to ablation of the avascular retina with the purpose of reducing the production of vasoproliferative factors (predominantly vascular endothelial growth factor) from this area.…”
Section: Introductionmentioning
confidence: 98%
“…A previous report (10) , that evaluated the influence of cryotherapy and diode laser photocoagulation on the growth of rabbit eyes, found areas of intraretinal peripheral macrocystoid edema and chronic inflammatory reaction. However, the authors performed between 15-20 cryo burns in each eye, with evaluation of histological sections after 10 weeks of follow up.…”
Section: Discussionmentioning
confidence: 99%